In the garden: capacities that contribute to community groups establishing community gardens - Gerard Doyle (International Journal of Urban Sustainable Development, 2022)
Based on case studies in Dublin, Ireland, this paper examines the motives for individuals to establish community gardens therein. The paper also outlines the capacities required for community groups to successfully establish and sustain community gardens in Ireland. These capacities include the involvement of individuals with a range of expertise, the presence of supportive community groups/organisations and state agencies, and access to resources, including land. The research findings, detailed in this paper, indicate that community gardens in urban settings encounter a number of challenges, including the absence of a mechanism for community groups to access land. The article provides a framework for community groups and community organisations to develop community gardens.